Awareness and perception of human papillomavirus and HPV vaccination and its program among reproductive-aged women in Taunggyi Township, Southern Shan State: a cross-sectional study with mixed-methods - Htwe, Yin Yin; Soe, Aung Kyaw (International Journal Of Community Medicine And Public Health, 2025)
Background: In Myanmar, cervical cancer is the second leading cause of cancer-related deaths among women. The effective prevention strategies are human papillomavirus (HPV) vaccination and screening programs. This study aimed to identify awareness and perception of HPV and HPV vaccination, and its program among reproductive-aged women. Methods: A cross-sectional study with mixed-methods was conducted at Taunggyi Township, Southern Shan State. About 340 reproductive-aged women from rural and urban areas were face-to-face interviewed. Two FGDs were conducted in selected areas. Results: Most respondents (322, 94.7%) heard of HPV, but knowledge of HPV infection, and its preventive measures were very low. Perception of HPV infection and its vaccination was good. The primary source of information about HPV and its vaccine was healthcare providers (70%), social media (14%) and teachers (8%). Common barriers to HPV vaccination were cost and lack of information. Respondents’ residence (p=0.018, 95% CI=0.06-0.08) and income (p=0.003, 95% CI=1.47-92.0) were the associated factors of knowledge of HPV, while education status (p=0.004, 95% CI=1.39-6.45) and own HPV vaccination status (p=0.031, 95% CI=1.07-1.16) were significantly associated with perception of HPV. Only respondents’ income was statistically significant with knowledge of HPV vaccination (p=0.001, 95% CI=1.03-1.11). As a result of thematic analysis, the overall information towards HPV vaccination program was satisfactory, despite the knowledge gap. Conclusions: This study indicated the need for targeted public health interventions that address knowledge gaps, enhance the opportunity for the role of healthcare providers and teachers and promote the HPV vaccination program by increasing accessibility and fostering community engagement.